Interview 10 - Abubakari, Yushawu
This file contains the interview notes with Chairman-one. Chairman-one (pseudonymize) is 31 years and have been scamming for 5 years. Chairman-one is married with one child and they live in his own house. Chairman has scammers working under him and those he works under too. The interview was done at the football part where he goes to play football on Sundays